N-NOSE Proves Effective for Early Cancer Detection: Real-World Data from Third-Party Medical Institutions - Nobushige Nakajo; Hideyuki Hatakeyama; Masayo Morishita; Eric di Luccio (Biomedicines)
Cancer remains a leading cause of mortality in Japan, yet participation in conventional screening programs is low due to invasiveness, cost, and accessibility. Non-invasive, affordable, and accurate methods for early cancer detection in asymptomatic individuals are urgently needed. This opinion manuscript evaluates nematode cancer testing, a novel urine-based screening test using the nematode Caenorhabditis elegans, for its potential to improve early cancer detection rates, based on real-world data published in a Japanese journal. Nematode cancer testing leverages the nematode’s ability to detect cancer-associated volatile compounds in urine, offering a highly sensitive, non-invasive screening approach. We analyzed data from a nationwide survey of PET-equipped medical institutions in Japan, comparing cancer discovery rates between nematode cancer testing-triggered and standard PET screenings. In nematode cancer testing-triggered PET screenings, the cancer discovery rate was 2.96%, significantly higher than the 1.31% observed in standard PET screenings. The apparent positive predictive value (PPV) of nematode cancer testing was calculated at 2.09%; when adjusted for PET/CT sensitivity, the actual PPV increased to approximately 11.7%. This reflects a screening efficiency 14.6 times higher than the general population’s cancer incidence. These findings indicate that nematode cancer testing successfully detects cancer in high-risk individuals and may encourage participation in further diagnostic evaluations. The recently published nationwide survey of PET-equipped medical institutions in Japan highlights the good performance of nematode cancer testing in cancer detection. As an opinion-type manuscript based on real-world data from Japan, this paper shows that nematode cancer testing has substantial potential as a cost-effective, minimally invasive primary cancer screening tool for asymptomatic populations. By enhancing early detection rates and screening efficiency, it addresses the limitations of traditional screening methods. Implementing nematode cancer testing could lead to improved cancer outcomes, particularly in populations with low participation in standard screening programs and resource-limited settings.